Market Reaction and Firm Value: A Governance, Risk and Compliance Disclosure Perspective - I Kadek Jonh Stiawan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to analyze the effect of Governance, Risk, and Compliance (GRC) disclosure on market reaction and firm value in the banking sector listed on the Indonesia Stock Exchange during the 2019–2023 period. The research sample was determined using purposive sampling, comprising 8 companies with observations over 5 years, resulting in a total of 40 annual reports. Data were collected through documentation of annual reports and analyzed using multiple linear regression. The results indicate that governance disclosure, risk disclosure, and compliance disclosure simultaneously have a significant positive effect on market reaction, suggesting that higher levels of GRC disclosure can enhance positive investor responses. Meanwhile, only governance disclosure and risk disclosure have a significant positive effect on firm value, whereas compliance disclosure does not show a significant impact. These findings align with positive accounting theory, which states that managers strategically use information disclosure to influence investor perceptions, increase market confidence, and drive firm value growth. This study provides important implications for company management to improve the quality of GRC disclosure as a market communication strategy and for investors in assessing the performance and growth potential of firms.